The Muslim’s meaning of life: How religious commitment and attachment to God influenced it? - Medina Chodijah; Salwa Mahalle (UIN Sunan Gunung Djati Bandung, 2023)
Various studies conclude that religion influences psychological well-being, including the formation of the meaning of one's life. This study aims to determine the extent of the influence of religious commitment and attachment to God with the meaning of life in adult Muslims. This study uses a quantitative approach, with 312 samples and uses 3 adaptation instruments from The Religious Commitment Inventory (RCI-10), The Attachment to God Inventory (AGI), and the Meaning in Life Questionnaire (MIL), which are then processed by descriptive statistics and correlation and regression techniques. The results show that 56.1% of the sample has a high religious commitment, while commitment to God has two dimensions: avoiding intimacy, where 53.5% of the sample was on the high scale and the dimension of anxiety about abandonment, where 87.2% lied on the low scale. In the meaning of life variable, 54.2% of the sample has a meaning of life on a high scale. There is a significant relationship between religious commitment to the meaning of life and attachment to God with the meaning of life. It can be concluded that religious commitment and attachment to God affect the meaning of one's life. Even though, Religious commitment has a greater influence on the meaning of life, which contributes 24.3%, while attachment to God only contributes 1.7%. The limitation in this study is that the instrument of attachment to God uses a general instrument that applies to all religious, so it is recommended for further research to use and develop an instrument of attachment to God that specifically refers to Islamic characteristics.